Global and local impacts of UK renewable energy policy - Ward, D; Inderwildi, O (2013)
Energy policies within one country or region can have significant global impacts, with unforeseen consequences. As an example, the EU requirements for 20% of final energy to be derived from renewable sources by 2020 feeds in to a UK target for renewable energy to make up 15% of UK final energy demand by 2020; the implications of this are investigated and found to have global repercussions. In order to achieve the UK target it is essential that the existing strategies for delivering wind power and coupling it to the grid are successful but there is an additional, greater, challenge. A large part of the UK renewables target will need to be met by the use of biomass and we show here that the amounts of biomass needed far exceed the supply capacity of the UK; imports will dominate the supply. The imports required are far greater than present day UK imports of coal with substantial potential implications; globally for biomass markets with potential impact on food supply and deforestation, and locally for UK infrastructure in shipping, ports, rail, road freight, electricity transmission networks and the coal industry. The way that a single country's response to a regional energy strategy can have global implications are investigated using one reference scenario for future UK fuel needs as an example. A strong outcome is that to implement this level of rapid change in the energy supply chain whilst avoiding negative impacts in a rapidly expanding global market there is a need for synchronisation of policies across economies as a whole, including anticipated effects beyond national borders, rather than policy measures in separate, isolated areas such as energy. © The Royal Society of Chemistry 2013.